The cucumber for Java book behaviour-driven development for testers and developers - Rose, Seb; Wynne, Matt; Hellesoy, Aslak (Pragmatic Bookshelf, 2015)
Cucumber - the popular, open-source tool that helps teams communicate more effectively with their customers - now has a Java version, and our bestselling Cucumber Book has been updated to match.